Winning by Intelligence: Leveraging the Innovative Advantages of Intelligent Transformation in Market Competition - Jingwen Lv; Lu Feng; Wei Xiao; Wei He (Systems)
Intelligent transformation plays an important role in enhancing innovation capabilities. This study utilizes data from 5000 A-share firms in China to investigate the effects of intelligent transformation on innovation capability and to elucidate the underlying mechanisms. We find that (1) there is a positive relationship between intelligent transformation and innovation capability. Furthermore, pursuing profit maximization and sustainable competitive advantage drives firms to capitalize on the technological dividends of intelligent transformation to enhance substantive innovation capability. (2) Intelligent transformation affects the innovation capability and structure through the mechanism of total factor productivity and market competition. (3) Within the intelligent transformation, non-state-owned enterprises exert a stronger influence on enhancing innovation capability, but state-owned enterprises remain the primary drivers of substantive innovation. The synergistic effect of intelligent transformation, combined with the scale advantages of large enterprises, create substantial opportunities for firms to enhance their innovation capability. Additionally, intelligent transformation notably enhances both the innovation capability and the innovation quality of labor-intensive enterprises. While capital-intensive enterprises experience significant improvements in their overall innovation capability, their substantive innovation capability has not shown comparable advancements. These findings contribute to a more accurate evaluation of the effects of intelligent transformation on innovation capability. The findings also help cultivate differentiated competitive advantages and drive high-quality development through intelligent empowerment.